From Resource-Based View to Practical Strategies: Internal Service Quality, Corporate Image, and Organizational Performance at Pakistan Railways - Asghar, Umair; Ullah, Naqeeb; Ahmed, Ahmad (2024)
This study, grounded in the Resource-Based View (RBV) theory, investigates the strategic impact of Internal Service Quality (ISQ) on Organizational Performance (OP), with a specific focus on Corporate Image (CI) as a mediator. Conducted at Pakistan Railways' Head Quarters in Lahore, the research employed purposive sampling, involving 325 permanent employees. SmartPLS 4 was utilized for data analysis. The results revealed that all hypotheses were statistically significant including the identification of corporate image as a significant partial mediator in the relationship between ISQ and OP. Aligned with RBV principles, the study emphasizes the strategic role of ISQ in enhancing OP. Practical implications highlight the importance of a strategic emphasis on ISQ, with a focus on leadership, integrated marketing communications, stakeholder engagement, and continuous monitoring for sustained improvements. These insights provide actionable strategies, particularly beneficial for entities like Pakistan Railways, aiming to optimize internal service quality to foster a positive external image, and enhance overall organizational performance.